(Neo)Liberal populism and Ireland's 'squeezed middle'. (April 2020) - Meade, Rosie R.; Kiely, Elizabeth
Acknowledging definitional problems associated with the concept of 'populism', this article shifts the analytic gaze away from actors or politics that are conventionally characterised as populist, on to an analysis of the doing of populism by those who typically evade the populist label. Tracing the discursive construction of the 'squeezed middle' in Irish mainstream media and parliamentary debates between January 2014 and March 2019, the authors analyse how this signifier was mobilised to fuel and foment ressentiment among middle-earning taxpayers. This article analyses how the discourses of the 'squeezed middle' functioned ideologically, as a form of anti-welfare populism, redirecting blame for middle-class ontological and material insecurities on to unemployed welfare recipients who were depicted as immoral, lazy and insulated from hardship. This article highlights how populism operates from the so-called moderate centres of liberal democracy and not exclusively from the political margins. Irish political and media narratives of the 'squeezed middle' are seen as part of a larger project whereby damaging myths about the unemployed are propagated in service of ideological class warfare; legitimising neoliberal austerity and normalising unequal economic relations.